Strain-induced structure and oxygen transport interactions in epitaxial La0.6Sr0.4CoO3−δ thin films - Yurii P. Ivanov (Nature Portfolio, 2020)
Strain engineering can enhance oxygen transport in cathodes in solid oxide fuel cells. Here, atomic scale imaging is used to probe local structures in tensile- and compressive-strained La0.6Sr0.4CoO3-δ films, revealing higher oxygen vacancy concentration in tensile films, and vacancy ordering.